2017
DOI: 10.1021/acs.nanolett.7b00233
|View full text |Cite
|
Sign up to set email alerts
|

Pressure–Temperature Phase Diagram of Vanadium Dioxide

Abstract: equally to this work. AbstractThe complexity of strongly correlated electron physics in vanadium dioxide is exemplified as its rich phase diagrams of all kinds, which in turn shed light on the mechanisms behind its various phase transitions. In this work, we map out the hydrostatic pressuretemperature phase diagram of vanadium dioxide nanobeams by independently varying pressure and temperature with a diamond anvil cell. In addition to the well-known insulating M1 (monoclinic) and metallic R (tetragonal) phases… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(51 citation statements)
references
References 28 publications
(86 reference statements)
6
40
0
Order By: Relevance
“…Finally, m 1 almost vanishes at high pressures ( figure 3(b)) indicating that the WLS merge with the QP. We emphasize that the proposed band diagram not only explains our experimental observations, but is also consistent with recent resistivity measurements that demonstrate the thermally activated character of the conductivity below T c for pressures up to 20 GPa [36,47]. The resistivity behavior implies only the existence of an energy gap leading to the decrease in the number of thermally activated charge carriers upon cooling.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Finally, m 1 almost vanishes at high pressures ( figure 3(b)) indicating that the WLS merge with the QP. We emphasize that the proposed band diagram not only explains our experimental observations, but is also consistent with recent resistivity measurements that demonstrate the thermally activated character of the conductivity below T c for pressures up to 20 GPa [36,47]. The resistivity behavior implies only the existence of an energy gap leading to the decrease in the number of thermally activated charge carriers upon cooling.…”
Section: Discussionsupporting
confidence: 92%
“…Figure 4(c) shows the frequencies of Raman modes as a function of pressure. The kinks around 12 GPa indicating an isostructural phase transition to a monoclinic M1′ phase [33,35] are in agreement with previous Raman studies [32,35,36], where transition pressures of 10-16 GPa are reported. Thus, our Raman results clearly indicate that VO 2 preserves monoclinic structure up to the highest pressure applied in our experiments.…”
Section: Raman Spectroscopysupporting
confidence: 92%
See 2 more Smart Citations
“…[1][2][3] Vanadium oxides usually possess several oxide phases, including VO, VO 2 , V 2 O 3 , V 2 O 5 , V 3 O 7 , V 4 O 9 , and V 6 O 13 . Vanadium oxide is among these smart materials which can tune its electrical and optical properties by applying external stimuli, such as heat or pressure.…”
Section: Introductionmentioning
confidence: 99%